Prototype of Automatic Watering and Fertilizing System for Oil Palm Seeds Based on Internet of Things - Muhammad Daud; Muhammad Yusril Zulfikar; Arnawan Hasibuan; Muzamir Isa (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2023)
Watering and fertilizing are very important to maintain the quality of the oil palm seeds. If the oil palm seeds are not watered regularly the soil will dry out while the oil palm seeds generally need to maintain adequate soil moisture and require a loose textured soil medium. So far, farmers have not optimally fulfilled the needs for water and fertilizer for oil palm seeds because they still use manual and traditional methods. Technological developments have made it possible to create irrigation and fertilization techniques automatically. In this study, a prototype of an automatic watering and fertilizing system was designed and realized for oil palm seedlings using the NodeMCU ESP8266 as the main controller in addition to RTC, humidity sensors, relays, water pumps, LCDs, and smartphones. RTC is used for fertilization scheduling, humidity sensors to sense soil moisture levels, relays as automatic switches that turn on and off pumps, water pumps to pump water and liquid fertilizer, LCD to display information, and smartphones to monitor conditions and processes of watering and fertilizing coconut seedlings palm. The test results show that the prototype tool can work well. When the soil moisture is read by the humidity sensor less than 30% (dry soil condition) then pump one is activated and when the soil moisture is more than 60% (wet soil condition) then pump one turns off. Furthermore, fertilization can take place according to a predetermined schedule where the second pump will automatically activate with a duration of 20 seconds for each fertilization period.